Strategies for Activities to be Conducted in the First 72 Hours After a Disaster: Türkiye - Feyza Betül Yurtlu; Başak Öztürk; Emel Güven; Tamer Eren (Doğal Afetler ve Çevre Dergisi)
Disasters are events that disrupt normal life and cause physical, economic, and social losses to people. Due to its location, Turkey is exposed to many disasters. This makes it important to successfully carry out the disaster management process. Planning what to do before and after a disaster and taking the necessary precautions are of great importance in the disaster management process. Strategies to be implemented in the first 72 hours, which is the most critical time period for search and rescue activities, are one of the most important parts of the process. Activities to be carried out within the first 72 hours represent a critical period for the management and commencement of the recovery process after a disaster. Resolving situations such as rapid rescue and first aid, ensuring communication infrastructure, meeting emergency needs, damage assessment and evaluation, ensuring community safety, and establishing a coordination center are vital within the first 72 hours after a disaster. This study encompasses the determination of strategies to be implemented in the critical first 72 hours after a disaster occurs. Multi-criteria decision-making methods were utilized in this study. The criteria influencing the determination of intervention strategies were weighted using the Analytic Hierarchy Process (AHP) method. The strategies developed in line with the weighted criteria were then prioritized using the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method. As a result of weighting the criteria with the AHP method, disaster severity ranked first, followed by the type of disaster in second place. In the ranking of strategies with the TOPSIS method, rapid rescue and first aid ranked first, and establishing a coordination center ranked second. In this way, we aim to achieve effective results in the shortest time by determining the priority order of activities.